Costs, quantity and toxicity: Comparison of pesticide indicators collected from FADN farms in four EU-countries. (September 2019) - Uthes, Sandra; Heyer, Ines; Kaiser, Annemarie; Zander, Peter; Bockstaller, Christian; Desjeux, Yann; Keszthelyi, Szilárd; Kis-Csatári, Eszter; Molnar, Andras; Wrzaszcz, Wioletta; Juchniewicz, Monika
Highlights: Data on farm-level pesticide use are scarce. We collected for the first time farm-level pesticide use data from 416 FADN farms. Farm-level indicators related to pesticide use, costs and toxicity were developed. Pesticide costs are not a sufficient proxy for pesticide use or toxicity. Evaluations should always look at pesticide use and toxicity simultaneously. Abstract: There is a growing demand in the last years for farm-level sustainability data reflected in various initiatives from farmers, science and food industries. An alternative to creating new tools and indicator assessment frameworks is to further develop existing farm monitoring systems, such as the EU-wide Farm Accountancy Data Network (FADN), towards inclusion of sustainability-related data. This article reports on a study carried out within the EU-project FLINT comparing indicators for pesticide costs, application quantity and pesticide toxicity calculated for 416 farms in four EU countries (France, Germany, Hungary, Poland). The farm sample was a non-representative subsample of the national FADN samples in these countries. Major focus of the comparison was to analyse the suitability of the indicators for implementation in a large so-far primarily economic farm-level monitoring system, such as the FADN. The FADN currently includes farm-level expenditure for crop protection as the only indicator with reference to pesticides. We show that it is possible to extend the current FADN with reasonable effort towards indicators for pesticide application quantity (pesticide usage, treatment index) and pesticide toxicity (here exemplarily used: lethal dose 50 in rats), while the data demands of more elaborated indicators could not be met with the current system. The correlation between indicators, reflecting the extent to which indicators come to the same conclusion, was small between pesticide costs and pesticide usage or toxicity, thus the use of pesticide costs as an ecological indicator, as was done in other studies, cannot be recommended. A combined consideration in the FADN system of pesticide quantity and toxicity, which showed moderate correlation, could be a suitable approach instead.